The Impact of Using the Internet for Learning for Students with Technology Acceptance Model (TAM) - O’Dell, Dominique Garcia; Sulastri, Tri (Three E Science Institute, 2019)
The development of the internet can provide convenience to humans in general, and students as one of the educational academics can provide changes in their life processes. The technique used in this study is Generalized Least Squares (GLS), which is proxied by using asymptotic covariance matrix data. The purpose of the study is to analyze the impact of the use of technology, in this case, is the internet in the learning process carried out by students. There are four constructs used in the TAM research, namely Perceived Ease of Use, Perceived Usefulness, Attitude Toward Using, and Actual Technology Usage. The research has three indicators for each latent variable. In this case, the latent variables are four. Then it can conclude that the number of samples used is 120. The sampling technique in this study uses Nonprobability sampling. The research hypothesis will test by analysis of SEM (Structural Equation Model) with the IBM AMOS (Analysis of Moment Structure) Program. The technique for using Generalized Least Squares (GLS), which is proxied by using the asymptotic covariance matrix data. From the results of the study, it found that this model has shown an overview of the aspects of the behavior of internet users that use for practical learning, where many users can efficiently operate the internet because it fits with what they need. Technology Acceptance Model (TAM) provides a reliable and straightforward explanation in accepting the technology and behavior of its users.